Partisipasi dalam Promosi Kesehatan pada Kasus Penyakit Demam Berdarah (DB) Ditinjau dari Pemberdayaan Psikologis dan Rasa Bermasyarakat - Francisca M. Josef; Tina Afiatin (Faculty of Psychology, Universitas Gadjah Mada, 2010)
Dengue Fever (DF) and its severe form, Dengue Haemorrhagic Fever (DHF), are major causes of morbidity and mortality for human beings. The cases of DF illness always increases in every year, especially when flood disaster occurred. Geographic position of Indonesia in tropical area made every province is DF endemic area. In 1997, there were 31.784 people and 156.697 people in 2007 who suffered from DHF. The Indonesian government conduct the community empowerment program as follows trainings for cadres of DHF prevention (Jumantik PSN DBD) in the communities and conduct the DHF prevention campaign in the schools in order to decrease the case number of DHF patients. The aims of this research as follows: (1) to know the influence of the Psychological Empowerment to the Participation in Health Promotion on the Disease Case of DF; (2) to know the influence of the Sense of Community to Participation in Health Promotion on the Disease Case of DF; and (3) to know the effective contribution from both Psychological Empowerment or Sense of Community toward Participation in Health Promotion on the Disease Case of DF. The participants of this research were 137 women with specific criteria: married, high school as the minimum education level, and has their own income. This research was conducted in Sleman District, the specific coverage area in Community Health Center (Puskesmas) of Gamping, Depok, Mlati, Kalasan, and Prambanan. The result of regression analysis shown: (1) Both of the Psychological Empowerment and the Sense of Community have influenced on the Participation in Health Promotion on the Disease Case of DF (R=0,436; p < 0,01), (2) the Psychological Empowerment has influenced on the Participation in Health Promotion on the Disease Case of DF (r=0,314; p < 0,01), (3) the Sense of Community has insignificant influenced on the Participation in Health Promotion on the Disease Case of DF (r=0,100; p > 0,05); (4) Both predictor variables contributes 19% to the criterion.